(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
The objectives of this study were to determine morphology of Japanese quail strains and hatchability rate and egg quality between commercial strain which is Poultry Progress Institute (IKTA) strain and White Texas strains of Japanese Quail (Coturnix japonica) rear in Malaysia. A total of 300 quails were randomly picked and the breastbone length, chest girth, body weight, body length, shank length and drum length were measured for the morphology. Then, 270 eggs of Commercial and White Texas strains were used to test the hatchability rate (n=150) and egg quality (n=120). The ratio of the parents of the quails between male and female of each type of strain were 1:3. The cleanliness, shape, weight, and texture of the eggshell were observed, weighed and measured. The eggs were incubated for 17 days (37.6 °C, 65% humidity). The shape index, egg weight, egg volume and eggshell surface were weighed and measured for the exterior trait of eggs. For interior trait, the albumen index, Haugh units, and internal quality units (IQU) were measured. Significant findings were observed in all of the features (P<0.05), except for the wing length in morphology. For hatchability rate, there was a high significant in the percentage of hatchability of incubated eggs, hatchability of fertile eggs and smoothness texture of the eggshell. In egg quality there was high significant in Haugh unit but low significant internal quality unit. The significant variability might be due from the genetic information that inherited from the parents. The IKTA and White strains were not the same in morphology, hatchability rate and interior trait of eggs but same exterior trait of eggs. In conclusion, this research is important in giving information about Japanese quail strain in Malaysia and more genetic study should be done in the future to determine good strain and increase understanding about quail strain.